Hydrovolt device and preparation method and application thereof
By loading the hydrophilic substrate with a pore structure with carbon material and forming hydrophobic and hydrophilic regions, a hydrovoltaic device with good output performance and mechanical flexibility at high ion concentrations is prepared, which solves the rigidity and brittleness of existing hydrovoltaic devices.
Patent Information
- Application Number
- CN202411753135.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
Existing hydrovoltaic devices are mechanically rigid and brittle, limiting their applications in the field of flexible wearables and have poor output performance at high ionic concentrations.
The hydrophilic substrate with a pore structure is immersed in a dispersion of carbon material with hydrophilic groups, and then dried to form a hydrophilic substrate loaded with a carbon material, and a hydrophobic region and a hydrophilic region are formed at both ends thereof, and the electrodes are connected to prepare a hydrovoltaic device.
It realizes that hydrovoltaic devices still have good output performance at high ion concentrations and provides mechanical flexibility support for their applications in the wearable field.
Smart Images

Figure CN119628459A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrovoltaic power generation, and in particular to a hydrovoltaic device and a preparation method and application thereof. Background Art
[0002] Hydrovoltaic devices are composed of hydrovoltaic hygroscopic materials and electrode materials. The hydrovoltaic hygroscopic materials have large specific surface area, good hydrophilicity and abundant nanochannels, and mainly include carbon materials, metal oxide materials, biofiber-based materials and composite materials, etc. The electrode materials have excellent conductivity, and mainly include carbon nanotube electrodes, copper electrodes, platinum electrodes and gold electrodes, etc.
[0003] However, existing hydrovoltaic devices all have certain mechanical rigidity and brittleness, which limits their application in the field of flexible wearables; and existing hydrovoltaic devices will fail to output at high ion concentrations, that is, the output performance of the hydrovoltaic device decreases with the increase of ion concentration in the solution, and can only output effective electrical energy in pure water or solutions with extremely low ion concentrations. Therefore, it is urgent to provide a hydrovoltaic device that is flexible and still has good output performance at high ion concentrations. Summary of the invention
[0004] In view of this, the present invention provides a hydrovoltaic device and a preparation method and application thereof to solve the problems of high rigidity and brittleness of existing hydrovoltaic devices and poor output performance under high ion concentration.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] In one aspect, the present invention provides a method for preparing a hydrovoltaic device, comprising the following steps:
[0007] (1) immersing a hydrophilic substrate having a pore structure in a dispersion of a carbon material having a hydrophilic group, taking it out and drying it to obtain a hydrophilic substrate loaded with the carbon material;
[0008] (2) immersing one end of the hydrophilic substrate loaded with carbon material in a hydrophobic solution, taking it out and drying it, so that the two ends of the hydrophilic substrate loaded with carbon material form a hydrophobic region and a hydrophilic region respectively;
[0009] (3) The end of the hydrophilic region is placed in water, and a first electrode is connected to the hydrophobic region to obtain a hydrovoltaic device.
[0010] Preferably, the immersion time in step (1) is ≥ 20 s.
[0011] Preferably, the drying temperature in step (1) is 60-200° C., and the drying time is ≥30 min.
[0012] Preferably, the immersion-drying process in step (1) is performed at least once.
[0013] Preferably, the drying temperature in step (2) is 30-100° C., and the drying time is >12 h.
[0014] Preferably, the carbon material having a hydrophilic group in step (1) comprises one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphite, and graphene having a hydrophilic group.
[0015] Preferably, the hydrophilic group includes one or more of a carboxyl group, a hydroxyl group, an amide group, an amino group, a sulfonic acid group, and a phosphoric acid group.
[0016] Preferably, the hydrophilic substrate having a pore structure includes one or more of plant fiber paper, sponge, and fiber cloth.
[0017] Preferably, the dispersion of the carbon material having a hydrophilic group in step (1) is obtained by dispersing the carbon material having a hydrophilic group in water.
[0018] Preferably, the dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300-500W, and the time is 30-120min.
[0019] Preferably, a surfactant is further added to the dispersion of the carbon material having a hydrophilic group, and the mass ratio of the surfactant to the carbon material having a hydrophilic group is 1-3:1.
[0020] Preferably, the surfactant includes one or more of sodium dodecylbenzene sulfonate, dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, and fatty acid salts.
[0021] Preferably, there is a gap between the first electrode and a boundary line between the hydrophobic region and the hydrophilic region.
[0022] Preferably, the hydrophilic substrate with a pore structure in step (1) is a pretreated hydrophilic substrate with a pore structure; the pretreatment includes ultrasonic cleaning and drying, the power of the ultrasonic cleaning is 60-120W, and the time is 10-60min; the temperature of the drying is 30-100°C, and the time is ≥10min.
[0023] On the other hand, the present invention provides a hydroelectric device prepared by any of the preparation methods described above.
[0024] In addition, the present invention also provides a hydrovoltaic device prepared by any of the preparation methods described above or the use of the hydrovoltaic device in hydrovoltaic power generation, taking a second electrode, placing the second electrode in a solution, and in the horizontal direction, there is a gap between the second electrode and the hydrophilic area.
[0025] The present invention provides a hydrovoltaic device and a preparation method and application thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0026] The output performance of the hydrovoltaic device prepared by the present invention can be improved with the increase of ion concentration; the hydrovoltaic device of the present invention is a single-electrode structure, and one of the electrodes is connected to the hydrophobic area of the hydrophilic substrate loaded with carbon material, and the other electrode is directly placed in the solution, and effective electrical energy output can be achieved without waterproof sealing treatment; and the hydrophilic substrate loaded with carbon material of the present invention has high mechanical flexibility, which provides a basis for the application of hydrovoltaic devices in the wearable field. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0028] Figure 1 It is a schematic diagram of the structure of the water-voltage device of the present invention;
[0029] Figure 2 This is a schematic diagram of the output performance of the hydrovoltaic device according to Example 1 of the present invention;
[0030] Figure 3 Schematic diagram showing the effect of the number of cycles of the immersion-drying process on the output performance of the hydrovoltaic device of the present invention;
[0031] Figure 4 It is a schematic diagram showing the effect of drying temperature on the output performance of a hydrovoltaic device during the preparation process of the plant fiber paper loaded with carbon material of the present invention;
[0032] Figure 5 It is a schematic diagram of the output performance of the hydrovoltaic device of the present invention in solutions with different salinities;
[0033] Figure 6 This is a schematic diagram of the flexibility test of the plant fiber paper loaded with carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0035] In one aspect of the present invention, the present invention provides a method for preparing a hydrovoltaic device, comprising the following steps:
[0036] (1) A hydrophilic substrate having a pore structure is immersed in a dispersion of a carbon material having a hydrophilic group, taken out and dried to obtain a hydrophilic substrate loaded with the carbon material.
[0037] In some embodiments of the present invention, the hydrophilic substrate with a pore structure is a hydrophilic substrate with a pore structure after ultrasonic cleaning and drying. Specifically, the hydrophilic substrate with a pore structure is ultrasonically treated in an ultrasonic cleaning machine filled with anhydrous ethanol and water for 10-30 minutes, for example, 10 minutes, 20 minutes, 30 minutes, etc., and the power of ultrasonic cleaning is 60-120W, for example, 60W, 90W, 120W, etc., and the pollutants and impurities in the micro-nano channels inside the hydrophilic substrate with a pore structure can be effectively removed by ultrasonic treatment; the drying temperature is 30-100°C, for example, 30°C, 50°C, 80°C, 100°C, etc., and the drying time is ≥10 minutes. The specific drying time can be appropriately adjusted according to the drying temperature, and there is no special limitation on this, and finally a clean and dry hydrophilic substrate with a pore structure is obtained.
[0038] In some embodiments of the present invention, the hydrophilic substrate with a pore structure includes one or more of plant fiber paper, sponge, and fiber cloth, wherein the pore structure is a structure with holes or channels, and the holes and channels in the hydrophilic substrate are used to attach carbon materials.
[0039] In some embodiments of the present invention, the immersion time is ≥ 20s, for example, it can be 20s, 1min, 2min, 5min, 60min, 24h, 48h, 96h, 168h, etc.; through experimental research, it is found that as long as the immersion time exceeds 20s, the output performance of the hydrovoltaic device under high ion concentration will not change significantly, so the immersion time can be adjusted according to actual conditions.
[0040] In some embodiments of the present invention, the drying temperature is 60-200°C, for example, it can be 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, 200°C, etc. Experimental studies have found that 60-200°C can achieve relatively excellent output performance, but when the drying temperature reaches 180°C, the hydrophilic substrate loaded with carbon material will turn yellow. Therefore, the preferred drying temperature is 60-160°C, more preferably 60-140°C; the drying time is ≥30min, for example, it can be 30min, 50min, 60min, 80min, 100min, 120min, etc. The specific drying time can be adaptively adjusted according to the drying temperature, and there is no special limitation on this.
[0041] In some embodiments of the present invention, the immersion-drying process is performed at least once, for example, once, twice, three times, four times or more times. It should be noted that the number of cycles of the immersion-drying process depends on the concentration of the carbon material having a hydrophilic group in the dispersion of the carbon material having a hydrophilic group. For example, when the concentration of the carbon material having a hydrophilic group is 1 mg / ml, the hydrovoltaic device can achieve the best output performance when the number of cycles of the immersion-drying process is limited to two times.
[0042] In some embodiments of the present invention, the dispersion of the carbon material having a hydrophilic group is obtained by dispersing the carbon material having a hydrophilic group in water.
[0043] In some embodiments of the present invention, the carbon material with hydrophilic groups includes one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphite, and graphene with hydrophilic groups, wherein the hydrophilic groups include one or more of carboxyl groups, hydroxyl groups, amide groups, amino groups, sulfonic acid groups, and phosphoric acid groups. For example, the carbon material with hydrophilic groups is a multi-walled carbon nanotube with a hydroxyl group, a multi-walled carbon nanotube with a carboxyl group, a single-walled carbon nanotube with an amide group, and the like. It should be noted that the carbon materials with hydrophilic groups used in the present invention are all purchased from the market.
[0044] In some embodiments of the present invention, the dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300-500W, and the time is 30-120min. The ultrasonic dispersion power can be, for example, 300W, 350W, 400W, 450W, 500W, etc. If the ultrasonic dispersion power is too low, the dissolution degree of the carbon material with hydrophilic groups is poor, and the utilization rate of raw materials is reduced; the ultrasonic time can be 30min, 60min, 90min, 120min, etc., which can be adjusted according to actual conditions. By performing ultrasonic dispersion under this limited condition, the carbon material with hydrophilic groups can be better dissolved.
[0045] In some embodiments of the present invention, a surfactant is further added to the dispersion of the carbon material having a hydrophilic group, specifically, the carbon material having a hydrophilic group and the surfactant are mixed and dispersed in water, wherein the surfactant comprises one or more of sodium dodecylbenzene sulfonate, dioctyl sodium sulfosuccinate, sodium dodecyl sulfate, sodium hexadecyl sulfate, and fatty acid salts, and there is no special limitation on this.
[0046] Among them, the mass ratio of the surfactant to the carbon material having a hydrophilic group is preferably 1-3:1, for example, it can be 1:1, 2:1, 3:1, etc. It is found through experiments that the dispersion of the carbon material having a hydrophilic group obtained without adding a surfactant has a stratification phenomenon, and the dispersion of the carbon material having a hydrophilic group obtained after adding a surfactant has better stability, but has no obvious effect on the output performance of the final hydrovoltaic device. Therefore, whether to add a surfactant can be determined according to actual conditions.
[0047] (2) One end of the hydrophilic substrate loaded with carbon material is immersed in a hydrophobic solution, taken out and dried, so that a hydrophobic region and a hydrophilic region are formed at both ends of the hydrophilic substrate loaded with carbon material, respectively.
[0048] In some embodiments of the present invention, the hydrophobic solution includes, but is not limited to, silicone hydrophobic agents, fluorocarbon hydrophobic agents, polyether hydrophobic agents, and hydrophobic inorganic materials, which are not particularly limited and can be purchased on the market.
[0049] In some embodiments of the present invention, the drying temperature is 30-100°C, for example, 30°C, 40°C, 60°C, 80°C, 100°C, etc., and the drying time is greater than 12 hours. It should be noted that the drying in this step can be air-dried at room temperature or placed in an oven for drying, and the drying time can be appropriately adjusted according to the drying method and drying temperature.
[0050] In some embodiments of the present invention, a hydrophobic region and a hydrophilic region are formed at both ends of a hydrophilic substrate loaded with a carbon material, respectively. There is no special limitation on the ratio of the lengths of the hydrophobic region and the hydrophilic region. For example, the ratio may be 1:1, 1:2, 2:1, 1:3, 3:1, etc., as long as two distinct regions, the hydrophobic region and the hydrophilic region, can be formed.
[0051] (3) The end of the hydrophilic region is placed in water, and a first electrode is connected to the hydrophobic region to obtain a hydrovoltaic device.
[0052] In some embodiments of the present invention, there is a gap between the first electrode and the boundary between the hydrophobic region and the hydrophilic region, and the first electrode is preferably connected to the hydrophobic region by clamping.
[0053] In another aspect of the present invention, the present invention provides a hydroelectric device prepared by any of the preparation methods described above. The hydroelectric device is prepared by the above-mentioned method. Therefore, the hydroelectric device has all the characteristics and advantages possessed by the above-mentioned method, which will not be repeated here.
[0054] In another aspect of the present invention, the present invention also provides a hydrovoltaic device prepared by any of the preparation methods described above or the application of the hydrovoltaic device in hydrovoltaic power generation, taking a second electrode, placing the second electrode in a solution, and in the horizontal direction, there is a gap between the second electrode and the hydrophilic area, and in actual use, an electrical device or an electrical storage device is connected between the first electrode and the second electrode, and when performing an output performance test, a test device is connected between the first electrode and the second electrode.
[0055] In an embodiment of the present invention, Figure 1 As shown, the hydrovoltaic device includes a hydrophilic substrate loaded with carbon material, a first electrode 7, a second electrode 5, a solution 4, a testing device 6 and a container 3 containing the solution, wherein the hydrophilic substrate loaded with carbon material forms a hydrophilic region 2 and a hydrophobic region 1, the hydrophilic region 2 is placed in the solution 4, the first electrode 7 is connected to the hydrophobic region 1, the second electrode 5 is placed in the solution 4, and in the horizontal direction, there is a gap between the second electrode 5 and the hydrophilic region 2; the first electrode 7 is preferably a clamped copper electrode so as to be clamped in the hydrophobic region 1.
[0056] When the hydrovoltaic device is working, the solution will quickly climb along the hydrophilic substrate loaded with carbon materials under the action of capillary force and evaporate at the junction of the hydrophilic area and the hydrophobic area. At the same time, since the hydrophilic negatively charged area of the hydrophilic substrate with a pore structure modified by the carbon material with hydrophilic groups is full of oxygen-containing functional groups, an overlapping double electric layer (EDL) will spontaneously form at the liquid-solid interface of the nanochannel. The negatively charged nanochannel will repel ions with the same charge in the water, but allow ions with the opposite charge to pass through (for water, H3O + ), when water flows through the nanochannel, a flow current is generated at the top electrode and a higher potential is generated, so the first electrode located at the top is positive and the second electrode located at the bottom is negative.
[0057] For salt solution, according to Debye-Hückel theory, as the ion concentration increases, the Debye length decreases, which will greatly reduce the repulsive performance of the negatively charged nanochannel, resulting in a decrease in the streaming potential. However, in the present invention, when the ion concentration in the solution increases, a galvanic effect will be formed between the active electrode copper and the hydrophilic substrate loaded with carbon material. During the reaction, the salt solution acts as an electrolyte for charge and mass transfer, forming a loop and having a significant impact on the output performance of the hydrovoltaic device. Through the redox reaction, chemical energy is converted into electrical energy. Therefore, the hydrovoltaic device of the present invention can output electrical energy in a salt solution with a higher concentration.
[0058] Example 1
[0059] This embodiment provides a method for preparing a hydrovoltaic device, comprising the following steps:
[0060] (1) treating the plant fiber paper in an ultrasonic cleaning machine containing anhydrous ethanol and water for 20 minutes, respectively, with an ultrasonic power of 80 W, and then drying it in a forced air drying oven at 60° C. for 20 minutes to obtain clean plant fiber paper;
[0061] (2) 0.1 g of multi-walled carbon nanotubes having hydroxyl groups and 0.3 g of sodium dodecylbenzene sulfonate were mixed and added to 100 ml of water, and then ultrasonically dispersed at a power of 450 W for 60 min to obtain a dispersion of a carbon material having a hydrophilic group;
[0062] (3) immersing the plant fiber paper of step (1) in a dispersion of a carbon material having a hydrophilic group for 2 minutes, taking it out and drying it at 60° C. for 60 minutes, repeating this step once to obtain a plant fiber paper loaded with a carbon material;
[0063] (4) One end of the plant fiber paper loaded with carbon material is immersed in the silica solution. Under the drag of capillary force, the hydrophobic solution climbs from bottom to top. The paper is taken out and placed in an oven at 60°C for 15 hours to form a hydrophobic region and a hydrophilic region at both ends of the plant fiber paper loaded with carbon material.
[0064] (5) Place the end of the hydrophilic area in water, take two copper electrode clips and connect them to the hydrophobic area and water respectively, connect them to an external test device, and perform an output performance test.
[0065] Based on the external test equipment, the output performance of the hydrovoltaic device of this embodiment was tested within 20 minutes. Figure 2As shown in the figure, in the early stage, due to the irregularity of the internal pores of the plant fiber paper loaded with carbon material, the output voltage curve fluctuates to a certain extent, and then tends to be stable; while the current curve initially has a sharp instantaneous current, and then tends to be stable after a large decrease. After 1200s, the hydrovoltaic device achieves an output voltage of 0.37V and an output current of 0.74μA.
[0066] Example 2
[0067] This embodiment is basically the same as Embodiment 1, with the only difference being that the immersion-drying process in step (3) is performed once.
[0068] Example 3
[0069] This embodiment is basically the same as embodiment 1, with the only difference being that the immersion-drying process in step (3) is performed three times.
[0070] Example 4
[0071] This embodiment is basically the same as Embodiment 1, with the only difference being that the immersion-drying process in step (3) is performed four times.
[0072] Example 5
[0073] This embodiment is basically the same as embodiment 1, with the only difference being that the immersion-drying process in step (3) is performed five times.
[0074] Example 6
[0075] This embodiment is basically the same as Embodiment 1, with the only difference being that the immersion-drying process in step (3) is performed six times.
[0076] Examples 1-6 were carried out with the number of cycles of the immersion-drying process in step (3) as a variable, and the output performance of the hydrovoltaic device of each example at the 20th minute was tested. Figure 3 .Depend on Figure 3 It can be concluded that when the concentration of multi-walled carbon nanotubes with hydroxyl groups is 1 mg / ml, when the immersion-drying process is carried out twice, the output performance of the hydrovoltaic device is optimal, with the output voltage reaching 0.37 V and the output current reaching 0.74 μA; when only one immersion-drying process is carried out, the fibers of the plant fiber paper loaded with carbon material have fewer carbon nanotube channels with hydrophilic groups and greater resistance; and when the immersion-drying process is repeated too many times, partial short circuits may occur inside the fibers of the plant fiber paper loaded with carbon material, making it impossible to effectively collect energy.
[0077] Example 7
[0078] This embodiment is basically the same as embodiment 1, the only difference being that the drying temperature in step (3) is 80°C.
[0079] Example 8
[0080] This embodiment is basically the same as embodiment 1, the only difference being that the drying temperature in step (3) is 100°C.
[0081] Example 9
[0082] This embodiment is basically the same as embodiment 1, the only difference being that the drying temperature in step (3) is 120°C.
[0083] Example 10
[0084] This embodiment is basically the same as embodiment 1, the only difference being that the drying temperature in step (3) is 140°C.
[0085] Example 1 and Examples 7-10 were carried out with the drying temperature in step (3) as a variable, and the output performance of the hydrovoltaic device of each example at 20 minutes was tested. Figure 4 .Depend on Figure 4 It can be concluded that within the range of 60-140°C, changes in drying temperature will not significantly affect the values of the open-circuit voltage and short-circuit current of the hydrovoltaic device.
[0086] Embodiment 11
[0087] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 0.001 mol / L NaCl solution.
[0088] Example 12
[0089] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 0.01 mol / L NaCl solution.
[0090] Example 13
[0091] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 0.1 mol / L NaCl solution.
[0092] Embodiment 14
[0093] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 0.6 mol / L NaCl solution.
[0094] Embodiment 15
[0095] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 1.0 mol / L NaCl solution.
[0096] Example 16
[0097] This embodiment is basically the same as embodiment 1, the only difference being that the water in step (5) is replaced with a 2.0 mol / L NaCl solution.
[0098] Examples 11-16 studied the output performance of the hydrovoltaic device at 20 minutes in solutions with different salinities. Figure 5 .Depend on Figure 5 It can be seen that under a series of NaCl concentrations, the open circuit voltage and short circuit current of the hydrovoltaic device increase with the increase of NaCl concentration. Specifically, with the increase of NaCl concentration, the open circuit voltage of the hydrovoltaic device increases from 0.447V to 0.703V, and the short circuit current of the hydrovoltaic device increases from 1.719μA to 13.289μA.
[0099] In addition, the present invention also conducted a flexibility test on the plant fiber paper loaded with carbon material prepared in Example 1. Figure 6 As shown, the plant fiber paper loaded with carbon material was subjected to bending and twisting operations, which showed high mechanical flexibility and could withstand a large degree of twisting.
[0100] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a hydrovoltaic device, characterized in that: The following steps are involved: (1) immersing a hydrophilic substrate having a pore structure in a dispersion of a carbon material having a hydrophilic group, taking it out and drying it to obtain a hydrophilic substrate loaded with the carbon material; (2) immersing one end of the hydrophilic substrate loaded with carbon material in a hydrophobic solution, taking it out and drying it, so that the two ends of the hydrophilic substrate loaded with carbon material form a hydrophobic region and a hydrophilic region respectively; (3) The end of the hydrophilic region is placed in water, and a first electrode is connected to the hydrophobic region to obtain a hydrovoltaic device.
2. The method for preparing a hydrovoltaic device according to claim 1, characterized in that: The immersion time in step (1) is ≥ 20 s; The drying temperature is 60-200°C and the drying time is ≥30min; The immersion-drying process is performed at least once.
3. The method for preparing a hydrovoltaic device according to claim 1, characterized in that: The drying temperature in step (2) is 30-100° C., and the drying time is >12 h.
4. The method for preparing a hydrovoltaic device according to claim 1, characterized in that: The hydrophilic substrate with a pore structure in step (1) includes one or more of plant fiber paper, sponge, and fiber cloth; The carbon material having a hydrophilic group includes one or more of multi-walled carbon nanotubes, single-walled carbon nanotubes, graphite, and graphene having a hydrophilic group; The hydrophilic group includes one or more of a carboxyl group, a hydroxyl group, an amide group, an amino group, a sulfonic acid group, and a phosphoric acid group.
5. The method for preparing a hydrovoltaic device according to any one of claims 1 to 4, characterized in that: The dispersion of the carbon material having a hydrophilic group in step (1) is obtained by dispersing the carbon material having a hydrophilic group in water; The dispersion is ultrasonic dispersion, the power of the ultrasonic dispersion is 300-500W, and the time is 30-120min.
6. The method for preparing a hydrovoltaic device according to claim 5, characterized in that: A surfactant is also added to the dispersion of the carbon material having a hydrophilic group, and the mass ratio of the surfactant to the carbon material having a hydrophilic group is 1-3:1; The surfactant includes one or more of sodium dodecylbenzene sulfonate, dioctyl sodium succinate sulfonate, sodium dodecyl sulfate, sodium hexadecyl sulfate, and fatty acid salts.
7. The method for preparing a hydrovoltaic device according to claim 1, characterized in that: There is a gap between the first electrode and a boundary line between the hydrophobic region and the hydrophilic region.
8. The method for preparing a hydrovoltaic device according to claim 1, characterized in that: The hydrophilic substrate with a pore structure in step (1) is a pre-treated hydrophilic substrate with a pore structure; The pretreatment includes ultrasonic cleaning and drying. The power of the ultrasonic cleaning is 60-120W and the time is 10-60min. The temperature of the drying is 30-100°C and the time is ≥10min.
9. A hydrovoltaic device prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a hydrovoltaic device prepared by the preparation method according to any one of claims 1 to 8 or the hydrovoltaic device according to claim 9 in hydrovoltaic power generation, characterized in that: A second electrode is taken and placed in the solution, with a gap between the second electrode and the hydrophilic region in a horizontal direction.